Arsenic-Doped SnSe Thin Films Prepared by Pulsed Laser Deposition - Prokeš, Lubomír; Kotrla, Magdaléna; Čermák Šraitrová, Kateřina; Nazabal, Virginie; Havel, Josef; Němec, Petr (American Chemical Society, 2021)
Pulsed UV laser deposition was exploited for the preparation of thin Sn50-xAsxSe50 (x = 0, 0.05, 0.5, and 2.5) films with the aim of investigating the influence of low arsenic concentration on the properties of the deposited layers. It was found that the selected deposition method results in growth of a highly (h00) oriented orthorhombic SnSe phase. The thin films were characterized by different techniques such as X-ray diffraction, scanning electron microscopy with energy-dispersive X-ray spectroscopy, atomic force microscopy, Raman scattering spectroscopy, and spectroscopic ellipsometry. From the results, it can be concluded that thin films containing 0.5 atom % of As exhibited extreme values regarding crystallite size, unit cell volume, or refractive index that significantly differ from those of other samples. Laser ablation with quadrupole ion trap time-of-flight mass spectrometry was used to identify and compare species present in the plasma originating from the interaction of a laser pulse with solid-state Sn50-xAsxSe50 materials in both forms, i.e. parent powders as well as deposited thin films. The mass spectra of both materials were similar; particularly, signals of SnmSen+ clusters with low m and n values were observed.
Tenké filmy SnSe dopované arsenem připravené pulzní laserovou depozicí
Keywords: mass spectrometry; clusters; SnSe; thin films; pulsed laser deposition; hmotnostní spektrometrie; klastry; SnSe; tenké vrstvy; pulzní laserová depozice